Aggregated power quality indicator for controlling a hybrid compensation system providing system services - Merkl, Ralf; Steglich, Michael; Paulsburg, Martin; Rehtanz, Christian; Franke, Jörg (IEEE PES Innovative Smart Grid Technologies Conference Europe, 2020)
In electric energy distribution, a defined level of power quality is to be maintained at all times to ensure reliable grid operation. Increased connection of power electronic feeders and loads as well as fluctuating power plants introduces time-varying power quality deviations. Within this article, we propose a concept for determining the present level of power quality and distributing the available power of a compensation system to individual services. Focusing on steady-state phenomena of power quality as harmonics, unbalance, frequency, voltage level and phase angle we calculate an aggregated indicator of the present power quality level. By applying well known procedures for calculation of individual power quality parameters we obtain required data for determining the aggregated power quality index. Restrictions are imposed by means of dead bands and limits specified by power quality standards.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Aggregated power quallity index; Grid support; Power quality; System services

A hybrid compensation system for provision of ancillary services in medium voltage grids - Böhm, Ralf; Steglich, Michael; Baucrnschmitt, Bjorn; Rehtanz, Christian; Franke, Jörg (2018 International Conference on Diagnostics in Electrical Engineering, Diagnostika 2018, 2018)
Medium voltage grids are subject to a change in load situation due to the installation of decentralized generation plants. Predominantly load symmetry, active and reactive power flows as well as requirements for the necessary capacity of earth fault compensation are affected. Decentralized generation connected through power electronics as well as consumers using switching power supplies cause distortions. Furthermore, electrical energy storage is gaining importance within rural distribution networks to compensate fluctuating generation plants. A hybrid compensation system can contribute to provision of adequate power quality by integrating several ancillary services into a single device. In this article the design of the hybrid compensation system is introduced and it is evaluated, which ancillary services in medium voltage distribution grids are likely to be provided using an inverter-based hybrid compensation system and a hybrid storage system.
CRIS-Team Scopus Importer:2023-03-07
Keywords: ancillary services; hybrid compensation system; hybrid storage system; power quality

A novel method to reduce the harmonic currents in the residual earth fault current during a single phase to ground fault in compensated grids - Steglich, Michael; Löwe, Christopher; Bauernschmitt, Björn; Rehtanz, Christian; Böhm, Ralf; Franke, Jörg (Proceedings of 2019 IEEE PES Innovative Smart Grid Technologies Europe, ISGT-Europe 2019, 2019)
This paper presents a new approach to reduce the harmonic currents during a single phase to ground fault in a compensated grid. The reduction of the harmonic component in the fault current improves network stability and possibly prevents a blackout. A model has been simulated in Matlab-Simulink with multiple current sources working as compensation system in a 20 kV medium voltage example grid. The simulation results show that the harmonic distortion of the grid voltage has a significant influence on the magnitude of the fault current. That may lead to exceeding the extinguishing limit if the distortion is too high. With the presented method it is possible to significantly reduce the harmonic current without intervening the grounding of the transformer and the zero system. Furthermore, it is possible to place the system anywhere within the grid, which leads to a high degree of flexibility and facilitates upgrading.
CRIS-Team Scopus Importer:2019-12-13
Keywords: Grid stability; Power distribution faults; Power distribution reliability; Power quality; System services

Control of a Hybrid Energy Storage System for a Hybrid Compensation System - Böhm, Ralf; Steglich, Michael; Rehtanz, Christian; Paulsburg, Martin; Datsevich, Sergey; Brunner, Benjamin; Franke, Jörg (Chemical Engineering & Technology, 2019)
The combination of two or more different energy storage technologies in a hybrid energy storage system appears to be advantageous if the combination of technologies fulfils the storage purpose better than a single storage technology. Herein, requirements regarding the performance of the storage system are determined for a hybrid compensation system for provision of system services in medium-voltage grids. In hybrid storage systems, a common control system ensures that the present storage technologies are utilized in such a way that total storage efficiency is highest and that usability of the application is maximized. The control system of a hybrid storage system consisting of a redox flow battery and high-speed flywheel storage is introduced and evaluated.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Energy management; Hybrid storage system; Power management

Control of a hybrid storage system (HSS) comprising a RedOx-Flow Battery and a High Speed Flywheel for a hybrid compensation system - Böhm, Ralf; Weindl, Christian; Franke, Jörg (2018 IEEE PES INNOVATIVE SMART GRID TECHNOLOGIES CONFERENCE EUROPE (ISGT-EUROPE), 2018)
CRIS-Team WoS Importer:2019-03-01

Cyber-physical compressed air systems enable flexible generation of compressed air adapted to demand of production - Böhm, Ralf; Weyrich, Sven; Franke, Jörg (7. WGP-Jahreskongress, 2017)
Industrial compressed air systems (CAS) embrace significant potential for saving both energy and cost due to their share of 7 % of the total industrial electricity consumption in Germany. In electric energy systems based on renewable generation plants supply and demand often do not occur in the same period of time. Consequently demand side management (DSM) is gaining importance whereby decentralized automation offers opportunities in industrial environments. Supply systems on industrial plants supply manufacturing equipment with compressed air, nitrogen and other technical gases, which partly can be obtained from air by deposition processes. Those systems consist of air compressors, gas separators, reservoirs and lines. With suitable dimensioning and by equipping with automation technology those systems can be used for demand side management purpose. In addition to basic operating parameters like current air pressure and status, those systems can process further information and create, for example, profiles on compressed air consumption over time. By enriching those profiles with data on pressure, volumes, system restrictions and current production requirements, the system control can identify the available potential for demand side management. Evaluation of operational strategies has to optimize conflicting objectives within the triangular relationship of storage design, control of the production according to price prospects and influencing or predicting the use of compressed air and technical gases obtained from air. For economical advantageousness of cyber- physical supply systems time flexible procurement prices for electric energy are required, enabling the utilization of use low prices in times of high supply. Costly production downtime due to inactive supply, caused by high electricity price has to be avoided mandatorily. Within the article, a conceptual approach for connection of CAS to production planning systems (PPS) will be presented and challenges as connecting demand forecasting and compressor control will be outlined.
Keywords: Energy efficiency; Neural network; Compressed air systems; Operating strategies; Demand forecast; Machine learning.

Demand-Side-Management by flexible generation of compressed air - Böhm, Ralf; Franke, Jörg (Procedia CIRP 63 ( 2017 ), 2017)
Industrial compressed air systems embrace significant potential for saving both energy and cost due to their share of approximately 7 % of the total industrial electricity consumption in Germany. As in electric energy systems based on renewable generation plants supply and demand often do not occur in the same period of time, volatile prices occur and demand side management is gaining importance. Decentralized automation offers opportunities in industrial environments for control of the equipment according to availability of electrical energy. Product-service systems on industrial plants supply manufacturing equipment with compressed air, nitrogen and other technical gases, which partly can be obtained from air by deposition processes. Those systems consist of air compressors, gas separators, reservoirs and lines. With suitable dimensioning and by equipping with automation technology those product-service systems can be used for demand side management purpose. In addition to basic operating parameters like current air pressure and status, those systems can process further information and create, for example, profiles on compressed air consumption over time. By enriching those profiles with data on pressure, volumes, system restrictions and current production requirements, the system control can identify the available potential for demand side management. Evaluation of operational strategies has to optimize conflicting objectives within the triangular relationship of storage design, control of the production according to price prospects and influencing or predicting the use of compressed air.
Keywords: Industrial compressed air systems; Energy flexibility

Feldlabor der Energiewende - SWW Wunsiedel GmbH und E|Home-Center arbeiten Hand in Hand an der Umsetzung des Wunsiedler Wegs Energie 2.0 - Bürner, Johannes; Böhm, Ralf (Umwelt-Technologie und Energie in Bayern, 2015)

Flexibilization of Biogas Plants through Intelligent Automation Generates Earning Opportunities - Spanheimer, Robert; Franke, Jörg; Erdmann, Diana-Maria; Schaidhauf, Ralph M.; Böhm, Ralf (Advanced Engineering Forum Vol. 19, 2016)
Due to guaranteed feed-in tariffs under the Renewable Energy Act and the feed-in precedence of renewable power generation plants the operation of biogas plants in Germany is currently plannable and economically advantageous. However, it is foreseeable that without this subvention biogas plants cannot compete with other regenerative plants such as photovoltaic and wind power plants on the open electricity market. Accordingly, it is of great importance for biogas plant operators to identify and occupy suitable niches to make full use of the unique features of their plants. Because of their predictable availability, those plants can particularly benefit of earning opportunities in times of high demand and contribute to grid stabilization. In order to keep the effort for plant operators as low as possible the automation of existing biogas plants can be extended and enabled to communicate with market platforms or control centers of the distribution system operator. Thus biogas plants can contribute to balancing group compensation not only for accounting purposes but factual by appropriate feed-in into the electrical network in consideration of actual demand.
Keywords: Biogas Plants; Digitalization; Direct Marketing; Energy Flexibility; Feed-In Tariffs

Innovative Flexible Heating System by the Use of Additive Plasma Coating Technology: Heating Where Heat Is Needed by Additive Metallization of Furniture and Walls - Braun, Thomas; Bürner, Johannes; Michl, Markus; Schaller, Lukas; Böhm, Ralf; Franke, Jörg (Proceedings of the 4th International Conference on Smart Energy Grid Engineering (SEGE), 2016)

Intelligente Versorgungssysteme für Druckluft und technische Gase - Böhm, Ralf; Javied, Tallal; Franke, Jörg (Industrie 4.0 Management : Gegenwart und Zukunft industrieller Geschäftsprozesse, 2017)

Inverter-based hybrid compensation systems contributing to grid stabilization in medium voltage distribution networks with decentralized, renewable generation - Böhm, Ralf; Rehtanz, Christian; Franke, Jörg (Electrical Engineering, 2016)
Medium voltage grids are subject to a change in load situation due to the installation of decentralized generation plants. Predominantly load symmetry, active and reactive power as well as the required capacity of earth fault compensation are affected. Inverter-based plants as well as consumers using switching power supplies or phase control cause distortions of frequency. Simultaneously, electrical energy storage is gaining importance within rural distribution networks to compensate fluctuating generation plants. A hybrid compensation system includes a transformer, a multi-phase inverter, diverse storage systems and a communication-capable control unit, which may be connected to the control center of the distribution system operator (DSO). It is object to current research activities to design and evaluate the functions of the superordinate control unit, which has to parametrize individual components, coordinate the energy flows between them and to embed several measuring instruments. Within the present work, basic considerations for design of system control are outlined.
Keywords: Active compensation systems; Ancillary services; Earth-fault compensation; Power quality

Investigation of Alternative Applications of Electrically Functionalized Surfaces Using the Plasma-Coating-Technology - Braun, Thomas; Böhm, Ralf; Praß, Julian; Baierl, Ullrich; Hahn, Dorothea; Franke, Jörg (Advances in Production Research - Proceedings of the 8th Congress of the German Academic Association for Production Technology (WGP), Aachen, November 19–20, 2018, 2018)
Keywords: Coating; Powder; Conductor track

Neue Ansätze für Energiemanagement und Energieeffizienz in der Produktion - Böhm, Ralf; Praß, Julian; Bürner, Johannes; Franke, Jörg (Umwelt-Technologie und Energie in Bayern, 2018)

Quo vehis, Electromobility? - Weigelt, Michael; Mayr, Andreas; Böhm, Ralf; Kühl, Alexander; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2018)
The spread of electromobility is still far behind the objectives and expectations of politics and society. Up to now, the relatively high vehicle costs, politically sanctioned energy prices, the limited vehicle ranges and the inconvenient charging process represent the major barriers. At the same time, several drivers exist, such as the superior efficiency, emission-free driving, conservation of fossil resources and the impressive driving enjoyment. This article summarizes the drivers and barriers of the electromobility from an ecological, economic and social perspective. Finally, the challenges for the technology development and the production technology are derive

Quo vehis, Elektromobilität? - Weigelt, Michael; Mayr, Andreas; Böhm, Ralf; Kühl, Alexander; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2018)
Die Verbreitung der Elektromobilität in Deutschland liegt nach wie vor hinter den Zielen und Erwartungen von Politik und Gesellschaft zurück. Bisherige Hemmnisse der Mobilitätswende sind vor allem die relativ hohen Anschaffungskosten von Elektroautos, die politisch sanktionierten Strompreise, die begrenzten Reichweiten sowie der noch wenig komfortable Ladevorgang. Dem stehen wiederum zahlreiche Treiber wie der überlegene Wirkungsgrad, das emissionsfreie Fahren, die Schonung fossiler Ressourcen sowie der beeindruckende Fahrspaß gegenüber. Der vorliegende Beitrag fasst die aktuellen Treiber und Hindernisse der Mobilitätswende aus ökologischer, ökonomischer und sozialer Perspektive zusammen und leitet daraus Herausforderungen an die Technologieentwicklung und Produktionstechnik a

Smart Energy and Grid: Novel Approaches for the Efficient Generation, Storage, and Usage of Energy in the Smart Home and the Smart Grid Linkup: Foundations, Principles, and Applications - Praß, Julian; Weber, Johannes; Staub, Sebastian; Bürner, Johannes; Böhm, Ralf; Braun, Thomas; Hein, Moritz; Michl, Markus; Beck, Michael; Franke, Jörg (Smart Cities: Foundations, Principles, and Applications, 2017)

Smart Factory Meets Smart Grid: Cyber-Physical Compressed Air Systems Enable Demand Side Management in Industrial Environments - Böhm, Ralf; Bürner, Johannes; Franke, Jörg (Energy Efficiency in Strategy of Sustainable Production, 2015)
In electric energy systems based on renewable generation plants supply and demand often do not occur in the same period of time. Consequently demand side management is gaining importance whereby decentralized automation offers opportunities in industrial environments. Compressed air systems on industrial plants consist of air compressors, compressed air reservoirs and compressed air lines. With suitable dimensioning those industrial compressed-air systems can be used for demand side management purpose. As power consumption of industrial air compressors ranges between a few and several hundred kilowatts each, swarms of communicatively connected air compressors can contribute to the stabilization of power grids. To avoid costly production downtime it is to ensure, that a reliable, non-disruptive supply of compressed air can be maintained at all time. Industrial compressed air systems equipped with automation technology and artificial intelligence, which hereinafter are referred to as Cyber-Physical Compressed Air Systems (CPCAS), allow new business models for utilities, industrial enterprises, compressor manufacturers and service providers. In addition to basic operating parameters like current air pressure and status, those systems can process further information and create, for example, profiles on compressed air consumption over time. By enriching those profiles with data on pressure, volumes, system restrictions and current production requirements (plans), the CPCAS can identify the available potential for demand side management. Ipso facto predictive power on electricity consumption is increasing. By providing the information obtained to the power company or a service provider, savings in electricity costs may be achieved. Expenses within the industrial company may be lowered further as compliance with agreed load limits is being improved by automatic shutdown of air compressors upon reaching the load limit. Within this article the structure of the aforementioned Cyber-Physical Compressed Air Systems is presented in more detail, relations between the major actors are being shown and possible business models are being introduced.
Keywords: Cyber-Physical Systems; Demand Side Management; Energy Efficiency; Industrial Compressed-Air Systems

StroMiS - Studie zur technisch-wirtschaftlichen Analyse der Stromerzeugung aus Mikrokraftwerken in Serienfertigung - Scholz, Michael; Kühl, Alexander; Höft, Annika; Landgraf, Maximilian; Schneider, Michael; Böhm, Ralf; Badel, Gregor; Lothes, Gerald; Angerer, Kerstin; Hohmann, Andrea; Simon, Peter; Konwitschny, Fabian; et al. (2019)

Superordinate Control Structure for Hybrid Compensation Systems - Böhm, Ralf; Paulsburg, Martin; Franke, Jörg (Advanced Engineering Forum Volume 19, 2016)
Medium voltage grids are subject to a change in load situation due to the installation of decentralized generation plants. Predominantly load symmetry, active and reactive power as well as the required capacity of earth fault compensation is affected. Inverter-based plants as well as consumers using switching power supplies or phase control cause distortions of frequency. Simultaneously electrical energy storage is gaining importance within rural distribution networks to compensate fluctuating generation plants. A hybrid compensation system includes a transformer, a multi-phase inverter, diverse storage systems and a communication-capable control unit, which may be connected to the control center of the distribution system operator (DSO). It is object to current research activities to design and evaluate the functions of the superordinate control unit, which has to parametrize individual components, coordinate the energy flows between them and to embed several measuring instruments. Within the present work, basic considerations for design of system control are outlined.
Keywords: Ancillary Services; Power System Harmonics; Digital Signal Processing